2021
DOI: 10.3389/fonc.2021.694749
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implementation of a 6D Treatment Chair for Fixed Ion Beam Lines

Abstract: PurposeTo verify the practicality and safety of a treatment chair with six degrees of freedom (6DTC) through demonstrating the efficacy of the workflow in clinical settings and analyzing the obtained technical data, including intra-fraction patient movement during the use of the 6DTC.Materials and MethodsA clinical study was designed and conducted to test the clinical treatment workflow and the safety of the 6DTC. Based on the demonstrated dosimetric advantages, fifteen patients with head and neck tumors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Most recently, Sun et al (31) presented results from clinical implementation of a chair positioning system targeted for head&neck cancers at the Shanghai Proton and Heavy Ion Center (SPHIC). Of 320 patients treated for head&neck, 15 showed a clear dosimetric benefit compared to a treatment with couch and fixed horizontal or 45°inclined beam line.…”
Section: Clinical Argumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, Sun et al (31) presented results from clinical implementation of a chair positioning system targeted for head&neck cancers at the Shanghai Proton and Heavy Ion Center (SPHIC). Of 320 patients treated for head&neck, 15 showed a clear dosimetric benefit compared to a treatment with couch and fixed horizontal or 45°inclined beam line.…”
Section: Clinical Argumentsmentioning
confidence: 99%
“…In their work, detailed stress simulations and experimental validations were performed to ensure highest safety of the components and accuracy of the treatment chair motion under patient load. Clinical implementation of the device with dedicated quality assurance protocol is reported in (46) and first experience with patient treatments is presented in (31).…”
Section: Brief Overview Over Existing Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical tests of this chair were performed by Sun et al. ( 111 ) to verify treatment and workflow feasibility. As optimal plans are possible with only a few fields, it is suggested that beam selection is more significant to the achievable dose distribution than the available number of fields or angles.…”
Section: Limitations and Avenues For Improvementsmentioning
confidence: 99%
“…A study by Sheng et al (110) report that rotational and translational positioning with a 6D treatment chair is comparable in alignment precision and reproducibility to a standard robotic treatment couch. Clinical tests of this chair were performed by Sun et al (111) to verify treatment and workflow feasibility. As optimal plans are possible with only a few fields, it is suggested that beam selection is more significant to the achievable dose distribution than the available number of fields or angles.…”
Section: Beam Delivery Systems Gantries and Fixed Beamlinesmentioning
confidence: 99%